Student writers’ metalinguistic repertoires in L1 education: Writerly choices and metalanguage in text interviews in Years 5 and 8 - Christensen, Mette Vedsgaard; Kabel, Kristine; Tannert, Morten (L1-Educational Studies in Language and Literature, 2026)
This study investigates student writers’ metalinguistic repertories in the context of L1 writing instruction in eight Danish schools. Data consists of text interviews with 48 focus students from Year 5 and Year 8, the students were interviewed about what they liked or found worked well in their own school texts. We investigate both the writerly choices the students chose to talk about and the metalanguage they used to do so. Our findings show that the students talk about the content, the structure and cohesion and about specific lexical choices in their writing, and that they most often use informal metalanguage to talk about content and lexical choices, while they use a formal metalanguage to talk about structure. More formal grammatical metalanguage is used to point to more general writing norms or teacher expectations. Our findings point to linguistic manipulations as a resource for expanding student writers’ metalinguistic repertoires. More extended metalinguistic repertoires seem to be related to (teacher perceived) writing competencies, however, we also see that specific instructional contexts seem to have the potential to expand metalinguistic repertoires, pointing to the importance of considering metalinguistic repertoires a key element in writing instruction and development.